2021
DOI: 10.1021/acs.nanolett.1c02284
|View full text |Cite
|
Sign up to set email alerts
|

Bulk-like ZnSe Quantum Dots Enabling Efficient Ultranarrow Blue Light-Emitting Diodes

Abstract: Blue-emitting heavy-metal free QDs simultaneously exhibiting photoluminescence quantum yield close to unity and narrow emission line widths are essential for next-generation electroluminescence displays, yet their synthesis is highly challenging. Herein, we develop the synthesis of blue-emitting QDs by growing a thin shell of ZnS on ZnSe cores with their size larger than bulk Bohr diameter. The bulk-like size of ZnSe cores enables the emission to locate in the blue region with a narrow emission width close to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 47 publications
0
95
0
Order By: Relevance
“…The detrapping rate constant in CdSe QDs with a larger core size depends not only on trap-depth but also on various other energetic parameters such as reorganization energy, temperature, etc . Indeed, in QDs having a larger size, surface trap-states are less accessible for the charge carriers since wave functions are localized in the core , ( vide infra ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detrapping rate constant in CdSe QDs with a larger core size depends not only on trap-depth but also on various other energetic parameters such as reorganization energy, temperature, etc . Indeed, in QDs having a larger size, surface trap-states are less accessible for the charge carriers since wave functions are localized in the core , ( vide infra ).…”
Section: Resultsmentioning
confidence: 99%
“…This increases the probability of a generation of multiexcitons in CdSe QDs with a smaller core size leading to fast Auger processes. In the case of QDs having a larger size, it is well-established that the wave functions of electron and hole are localized in the inner region of the core. , In the FLID plot of large sized CdSe/CdS/ZnS QDs, an increased occurrence of the high-intensity and high-lifetime component is observed due to neutral exciton recombination which can be attributed to charge carrier wave function localization in the core. As the core size decreases, the electron and hole wave functions penetrate to the core–shell interface leading to trapping and multiexciton generation, as evidenced by the low-intensity and low-lifetime component.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Gao et al 153 reported bulk like ZnSe/ZnS core-shell QDs exhibiting high quantum yields up to 95% with an ultra-narrow emission linewidth of 9.6 nm. 157 The QD-LEDs based on these ZnSe/ZnS QDs show a maximum EQE of 12.2% and a long operation lifetime, which is made possible by the growth of the ZnS shell. In spite of having a high efficiency and long lifetime, care must be taken while growing the core-shell QDs in order to lower the lattice mismatch between the core and the shell.…”
Section: Challenges Of Qd-based Ledsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Quantum-dot (QD) emissive layer (EML), one of the most key units in the QLEDs, has attracted much attention and various strategies are proposed to optimize the synthesis of QDs. [7][8][9][10][11][12] Thanks to the achievement…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–6 ] Quantum‐dot (QD) emissive layer (EML), one of the most key units in the QLEDs, has attracted much attention and various strategies are proposed to optimize the synthesis of QDs. [ 7–12 ] Thanks to the achievement of high‐quality QDs, QLEDs have gained huge progress and the performance is comparable with that of state‐of‐the‐art organic light‐emitting diodes. Especially, the red and green QLEDs have delivered the external quantum efficiency (EQE) over 20% and operating lifetime up to a few millions of hours.…”
Section: Introductionmentioning
confidence: 99%